Measurements of deformation, schlieren and forces on an OAT15A airfoil at pre-buffet and buffet conditions. Issue 1 (January 2021) - Accorinti, Alessandro; Baur, Tim; Scharnowski, Sven; Knebusch, Johannes; Dillinger, Johannes; Govers, Yves; Nitzsche, Jens; Kahler, Christian J.
Abstract: Self-sustained shock wave oscillations on airfoils, commonly defined as shock buffet, can occur under certain combinations of transonic Mach number and angle of attack due to the interaction between the shock and the separated boundary layer. To help understanding buffet physics, a rigid supercritical wing model (OAT15A) was investigated in pre-buffet and buffet conditions using a combined application of BOS (Background Oriented Schlieren), deformation and force measurements. From the observation via BOS of the change of the shock location and the extent of the boundary layer separation with the AoA (angle of attack), the transition from stable shock to buffet was detected. A comparison with other research groups at supposedly similar aerodynamic conditions highlighted a great disparity among them in terms of buffet onset, amplitudes of buffet oscillations, and flow development (motion of the mean shock location with the AoA) after the onset. The average and rms (root mean square) of the surface displacement were computed together with the effective geometric AoA, taking into account the static torsional deformation of the model and its support. Moreover, the spectra of the balance and deformation data showed the same buffet peak as in the BOS spectrum, indicating a coupling between structure and flow, which increased with the AoA.